Exploring the Interplay between Teacher Leadership and Self-Efficacy: A Systematic Literature Review (2013–2024) - Xue Luo; Bity Salwana Alias; Nor Hafizah Adnan (Education Sciences)
This systematic review rigorously explores the reciprocal relationship between teacher leadership and self-efficacy across a range of educational and cultural settings. Drawing on eleven peer-reviewed studies from 2013 to 2024 and guided by the PRISMA framework, the analysis substantiates a robust, bidirectional link: teacher leadership significantly bolsters self-efficacy, which, in turn, profoundly impacts educational practices and outcomes. The dynamics of this relationship exhibit considerable variation across cultural divides, with collectivist settings predominantly favoring a collaborative approach that enhances collective efficacy and teamwork, whereas individualistic contexts tend to prioritize personal achievement and empowerment. The findings highlight the imperative for culturally tailored professional development programs and affirm the critical influence of teacher self-efficacy in driving educational innovation and reform. Despite the richness of the insights presented, the studies’ limited sample sizes and the specificity of their educational contexts may temper the broader applicability of the conclusions. This review recommends that future research adopt longitudinal and mixed-methods approaches to deepen the understanding of these interactions across diverse cultural landscapes, thereby enriching the theoretical and practical implications for global educational advancement.